SOBRE RANKINGS Y ALGO MÁS - Fairlie Frisancho, Ebor (2011)
This article outlines the reasons why the universities of our country simply do not figure in the rankings for this foreign and we use the latest rankings of the Times Higher Education World University Ranking of London, recently published on 03 October, with the aim of performance put more items and get closer to the standards set internationally or going on the road to these.